The Escalation of Myocardial Infarction in Young Adults of Kashmir: A Multidimensional Analysis of Risks, Resilience, and Remedial Pathways - Shahid Shafi Rather (International Journal of Research in Medical Surgical Nursing, 2025)
Myocardial Infarction (MI), commonly perceived as a condition affecting older adults, is alarmingly increasing among younger populations worldwide. In Kashmir, a region heavily impacted by socio-political unrest, this issue is exacerbated by chronic stress, unhealthy lifestyle changes, and limited access to preventive care. This cross-sectional study of 500 young adults aged 20–45 diagnosed with MI aimed to uncover the role of modifiable risk factors and psychological resilience in disease progression and recovery. The study revealed that 72% of participants were male, and 68% were smokers. Sedentary lifestyles were prevalent, with 64% reporting physical inactivity. Clinically, 47% had hypertension, 52% had dyslipidemia, and 36% had a family history of heart disease. Psychological evaluations highlighted severe stress levels in 74% of participants, and resilience scores were significantly lower in MI patients compared to healthy individuals (47 vs. 62). Recovery outcomes showed that participants with higher resilience demonstrated faster recovery, better adherence to medications, and reduced complications. In contrast, those with low resilience struggled with managing lifestyle changes and adhering to treatment protocols. These findings underscore the need for holistic health policies in Kashmir, combining preventive measures, mental health support, and resilience-building interventions to combat the rising tide of premature cardiovascular disease.